2007
DOI: 10.1063/1.2709917
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ferroelectric properties of Na1∕2Bi1∕2TiO3-BaTiO3 single crystals by Ce dopings

Abstract: Ferroelectric single crystal of Na1∕2Bi1∕2TiO3-BaTiO3 (NBT-BT) and Ce doped NBT-BT have been grown by flux technique. It is found that the addition of Ce plays a significant role in improving the ferroelectric properties of NBT-BT crystals, (i) by improving the value of the dielectric constant at room temperature and at Tm (the phase transition temperature between antiferroelectric and paraelectric phases with dielectric maximum), (ii) by increasing the depolarization temperature (Td) and Tm, (iii) by increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Our crystals had a relatively large P r and a small E c compared with the reported values for other BNT-BT crystals [54,62,63]. It has been reported that the high-Po 2 TSSG method provides high-quality crystals with low concentrations of the vacancies of Bi and O due to a suppression of the defect-formation reaction at high temperatures during the crystal-growth process [46][47][48][49].…”
Section: Resultssupporting
confidence: 49%
“…Our crystals had a relatively large P r and a small E c compared with the reported values for other BNT-BT crystals [54,62,63]. It has been reported that the high-Po 2 TSSG method provides high-quality crystals with low concentrations of the vacancies of Bi and O due to a suppression of the defect-formation reaction at high temperatures during the crystal-growth process [46][47][48][49].…”
Section: Resultssupporting
confidence: 49%
“…A drawback of the quenching approach is the development of residual stress in samples, which in extreme cases can result in fracture and limit this strategy in real‐time applications 19,30 . None of the chemical modifications have resulted in a significant increase in both T F‐R and Q m 20‐24,31‐40 . The best improvements were an increase in Q m to ~600 with concurrent enhancement in T F‐R by 20 °C for 1 mole % Co 2 O 3 ‐added‐85(Na 1/2 Bi 1/2 )TiO 3 –12(K 1/2 Bi 1/2 )TiO 3 –3BaTiO 3 41 .…”
Section: Introductionmentioning
confidence: 99%
“…19,30 None of the chemical modifications have resulted in a significant increase in both T F-R and Q m . [20][21][22][23][24][31][32][33][34][35][36][37][38][39][40] The best improvements were an increase in Q m to ~600 with concurrent enhancement in T F-R by 20 °C for 1 mole % Co 2 O 3 -added-85(Na 1/2 Bi 1/2 )TiO 3 -12(K 1/2 Bi 1/2 ) TiO 3 -3BaTiO 3 . 41 Fe-and Mn-doping were documented to increase T F-R by 20 °C.…”
mentioning
confidence: 99%
“…Recently there have been a large number of publications in leading physics journals that claim different materials are ferroelectric, based upon the observation of a closed loop in the graph of switched charge Q versus applied electric voltage V . While most researchers are aware of the potential artefacts (outlined in classic texts such as Lines and Glass [1] Jaffe et al [2], or Fatuzzo and Merz [3]) associated with the measurement of polarisation-electric field (P-E) loops, there are still far too many articles [4][5][6][7][8][9][10][11][12][13][14][15] reporting completely meaningless coercive field and remanent polarization values extracted from cigar-shaped loops that are typical of lossy dielectrics and have very little to do with the true ferroelectric properties of the material studied. References [4][5][6][7][8][9][10][11][12][13][14][15] are an informal list of papers from only a few journals in the past two years; the real total of such artefacts published probably exceeds a hundred.…”
mentioning
confidence: 99%